Religion in Television: Mediated Religious "Kuliah Subuh” Program in Indonesia - Taufiqurrohim, Taufiqurrohim (FIKRAH, 2017)
In this contemporary life, television becomes an effective media of the da’wa or proliferation. The flourishing some of Islamic programs also effects to the order of the religious public life in Indonesian society. Using the descriptive analytical research, this essay investigates the process of religious proliferation program who become popular in society. It is started from the objective of some television channel to show “kuliah subuh”, a religious speech from an expert people that understand about Islamic religion or ustad after the dawn. Then the writer tries to find an effect of the media especially television to the audiences from the message of the program and their daily life expressions. Finally, “kuliah subuh” appears as a mediated religion which produces certain effects on religion in order to adapt it to television formats. It make the birth of transformations and paradoxes within the institutional model of religiosity.